Understanding the Structure and Mechanism of Formation of a New Magnetic Microbubble Formulation - Joshua Owen, Bin Zhou, Paul Rademeyer, Meng-Xing Tang, Quentin Pankhurst, Robert Eckersley, Eleanor Stride (Theranostics, 2012)
Magnetic nanoparticles and ultrasound contrast agents have both been used as vehicles for therapeutic delivery. More recently, magnetic microbubbles have been developed as a new theranostic agent which combines the advantages of the individual carriers and overcomes many of their limitations. In a previous study of gene delivery using magnetic microbubbles, it was found that a combination of magnetic liquid droplets and non-magnetic phospholipid microbubbles produced higher transfection rates than magnetic microbubbles. The reasons for this were not fully understood, however. The aim of this study was to investigate the hypothesis that conjugation between the droplets and the microbubbles occurred. A combination of optical and fluorescence microscopy and ultrasound imaging studies in a flow phantom were performed. No interaction between magnetic droplets and microbubbles was observed under optical microscopy but the results from the fluorescence and acoustic imaging indicated that magnetic droplets and microbubbles do indeed combine to form a new magnetically and acoustically responsive particle. Theoretical calculations indicate that the driving force of the interaction is the relative surface energy and thus thermodynamic stability of the microbubbles and the droplets. The new particles were resistant to centrifugation, of comparable echogenicity to conventional ultrasound contrast agents and could be retained by a magnetic field (0.2T) in a flow phantom at centre line velocities of ~6 cm s-1 and shear rates of ~60 s -1.